The extreme mobility of debris avalanches: A new model of transport mechanism. Issue 12 (11th December 2015) - Perinotto, Hélène; Schneider, Jean‐Luc; Bachèlery, Patrick; Le Bourdonnec, François‐Xavier; Famin, Vincent; Michon, Laurent
Abstract: Large rockslide‐debris avalanches, resulting from flank collapses that shape volcanoes and mountains on Earth and other object of the solar system, are rapid and dangerous gravity‐driven granular flows that travel abnormal distances. During the last 50 years, numerous physical models have been put forward to explain their extreme mobility. The principal models are based on fluidization, lubrication, or dynamic disintegration. However, these processes remain poorly constrained. To identify precisely the transport mechanisms during debris avalanches, we examined morphometric (fractal dimension and circularity), grain size, and exoscopic characteristics of the various types of particles (clasts and matrix) from volcanic debris avalanche deposits of La Réunion Island (Indian Ocean). From these data we demonstrate for the first time that syn‐transport dynamic disintegration continuously operates with the increasing runout distance from the source down to a grinding limit of 500 µm. Below this limit, the particle size reduction exclusively results from their attrition by frictional interactions. Consequently, the exceptional mobility of debris avalanches may be explained by the combined effect of elastic energy release during the dynamic disintegration of the larger clasts and frictional reduction within the matrix due to interactions between the finer particles. Key Points: Particles evolve morphologically during transport Fractal dimension decreases, whereas their circularity increases with distance Dynamic disintegration and particle interactions allow the flow mobility